2017
DOI: 10.1002/bdra.23607
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of gene–gene interactions between MTHFD1 and MTHFR in relation to anterior encephalocele susceptibility in Northeast India

Abstract: The data support our hypothesis of gene-gene interaction between MTHFD1 and MTHFR and the risk of AE. Together with the MTHFR haplotypes, MTHFD1 elevates risk in a progressive manner. The minor allelic frequencies of the MTHFD1 1958G>A and MTHFR 1298A>C in our populations were similar to those reported from Southeast Asian population, suggesting a possible explanation for the prevalence of this malformation in these regions. Birth Defects Research 109:432-444, 2017. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
(26 reference statements)
0
7
1
1
Order By: Relevance
“…Dutta et al through a case-control study comprising forty anterior encephalocele (AE) cases and eighty controls investigated whether the interaction between MTHFD1 and MTHFR results into susceptibility to AE in population from Northeast India. [39] In this study, 677C>T was not found to be an independent risk factor of AE. Besides, similar to the other two studies cited above, the prevalence of the C677TT genotype among cases was found to be zero or close to zero.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…Dutta et al through a case-control study comprising forty anterior encephalocele (AE) cases and eighty controls investigated whether the interaction between MTHFD1 and MTHFR results into susceptibility to AE in population from Northeast India. [39] In this study, 677C>T was not found to be an independent risk factor of AE. Besides, similar to the other two studies cited above, the prevalence of the C677TT genotype among cases was found to be zero or close to zero.…”
Section: Discussioncontrasting
confidence: 49%
“…Our study is in perfect match with studies by Hayati et al ., Sadewa et al ., and Dutta et al . [ 37 38 39 ] where no MTHFR C677 TT genotype was found. Hayati et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the observation of rare CNVs in some known NTD risk genes and pathways, including one-carbon metabolism, reinforces the validity of this strategy. Digenic variants have been observed in a number of mouse models of NTDs 38 as well as in human studies, suggesting synergistic deleterious effects of variants in genes involved in folate metabolism 39 or in PCP component genes. 40 While larger cohorts will be needed to reach statistical power necessary to pinpoint specific gene combinations indicative of individual risk, an oligogenic or polygenic model of SB risk is gaining traction and should be considered when evaluating genomic contribution.…”
Section: Discussionmentioning
confidence: 99%
“…La encefalocele frontal se debe a una alteración del cierre del neuroporo anterior durante la embriogénesis que resulta en la herniación o secuestro de tejido a través del frontículo frontal o foramen secum entre los días 26 a 28 de gestación 1- Estos defectos congénitos ocurren 1 por cada 13 000 nacimientos, 5 los reportes en América Latina señalan una prevalencia entre 1,1 a 4,5 por 10,000 nacimientos en poblaciones latinoamericanas 6 , mientras que en el sur de Asia 1 cada 3000 a 5000 nacimientos 7 . La localización más frecuente es en la región occipital (75%) 6 .…”
Section: Introductionunclassified